Integrating sustainable development to the suppliers by the supply chain sustainability GRAMEENPHONE Ltd. - Rahman, Nusrat (2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.